Evaluating the Effectiveness of Sinkhole Mitigation and Its Impact on the Local Community: A Case Study of the Armala Sinkhole, Pokhara, Nepal - Bhattarai, Mahendra; Baral, Sanjay; Adhikari, Badri (Himalayan Journal of Applied Science and Engineering, 2025)
Sinkholes are sunken areas or cavities that appear on level ground when soluble rocks beneath the surface dissolve, often forming suddenly and without warning. The Armala area, located in the Pokhara Formation, intersects with the Ghachock Formation, forming fluvio-lacustrine terraces along the Kali Khola valley with sediments of gravel, limestone, quartz, and gneiss mixed with calcareous silt, clay, and fine sand. A significant sinkhole event in 2013 devastated the Armala area, impacting the local community who faced severe challenges due to the extent and rapid formation of these sinkholes. This study aims to assess the effectiveness of sinkhole mitigation measures and their impact on the nearby community in Armala. This research evaluates the current state of sinkhole prone areas, the effectiveness of existing mitigation structures, and the community’s perception of these interventions. Field observations and surveys were conducted among 30 identified households to gather data from affected residents. Results indicate that while the mitigation efforts have positively influenced the community and reduced some immediate risks, challenges remain. Key observations reveal a need for improvement in both the number and condition of mitigation structures, many of which require reconstruction due to poor maintenance. The SPSS evaluation showed that Cronbach's alpha values exceeded 0.67 for all question groups, with an overall reliability of 0.7262, indicating consistent assessment. This study underscores the need for strengthened policies and sustained investment to enhance sinkhole mitigation and community resilience in affected areas.